Ziarah Makam dan Ritual Besangi : Makam Maulana Syeh Gauz Abdurrozak di Loang Baloq Lombok - Nuruddin, Nuruddin (UIN Mataram, 2023)
This study aims to determine the motivation of the community behind the besangi ritual during the pilgrimage to the Maqam of Maulana Syeh Gauz Abdurrozak and also to find out what is felt after making the pilgrimage to the grave. In this re-search, the method used is qualitative research method. By using data collection techniques namely observation, interviews, documentation and data analysis. As for the results of research on grave pilgrimages at Wali Maulana Syeh Gauz Ab-durrozak's Tomb which is in Loang Baloq, namely as a form of respect to remember the services of the saints in the process of Islamization in Indonesia, especially in Lombok. In addition, the tomb of the guardian is a medium for conveying wishes to Allah and obtaining blessings from the wali. Keywords: Ziarah, Makam, ritual, besangi, Lombok